Quality Of Audit In Public Sector Organizations: Trends And Article Analysis - Vitriyan Espa; Marsela Diaz; Soeprajitno, Raden Roro Widya Ningtyas (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2024)
This study purpose to explore and analysis the "characteristics of audit quality" through two questions: 1. what are the publication trends of audit quality-themed articles based on research contributors, and 2. what are the developments in research related to audit quality up to the present. The study employs a systematic literature review using keywords that describe the article topic coverage to identify trends in audit quality characteristics. The sample consists of 26 articles from the database SCOPUS from 2011 to 2020 on audit quality. The results indicate that University Utara Malaysia's contributions dominate among institutional contributors to the articles, article contributions are predominantly from Indonesia by country, and contributions are dominated by the International Journal of Economics Research based on journal source. The final results related to audit quality show variability with appropriate testing. This research empirically contributes to the development of literature and aids in analyzing audit quality-related research.